واقع السِّياحَة الدَّاخليَّة في سورية دراسة ميدانية في محافظة اللاذقية - خضرة, جلال; سليطين, فاطر; حسن, باسم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
على الرغم من المقومات السياحية والطبيعية التي تمتلكها سورية وتمثل عناصر جذب سياحي، لا تزال صناعة السِّياحَة ناشئة وحصتها من الطلب العالمي متواضعة قياساً بالإمكانات، ولا تزال السِّياحَة تعتمد أساساً على السِّياحَة المحلية والدَّاخليَّة والتي تشكل النسبة الأكبر من إجمالي الطلب السياحي في سورية، هذا ما دفعنا لدراسة واقع السِّياحَة الدَّاخليَّة في سورية للتعرف على نقاط القوة والضعف والمعوقات أو التحديات التي تواجهها ومن ثم تقديم مقترحات وحلول مبنية على الدراسة الميدانية ومن آراء المواطنين وتوفير متطلبات السِّياحَة الدَّاخليَّة ومقومات نجاحها. أهم النتائج التي وصلت إليها: يعتبر مستوى الدخل أحد أهم العوائق أمام السِّياحَة الدَّاخليَّة إلى جانب عدم توفر وقت الفراغ، كما تُفضِّل النسبة الأكبر من العينة المدروسة السِّياحَة الساحلية، وهناك ضعف دور وسائل الإعلام في التعريف بالمقاصد السياحية والترويج للمُنتَج السياحي السوري. Although the tourism and natural resources owned by Syria and represent elements of tourist attraction, tourism industry is still emerging and its share of the global demand is modest compared to its potentials, and tourism continues to rely mainly on domestic tourism, and the Interior, which constitutes the largest proportion of the total demand for tourism in Syria, this is why we have to study the reality of domestic tourism in Syria to identify the strengths and weaknesses and obstacles or challenges it faces , and then we offer suggestions and solutions based on field study and the views of citizens and the requirements for domestic tourism and its success. The most important results are: income level is one of the main obstacles to domestic tourism as well as the lack of free time, and the larger proportion of the sample studied prefer coastal tourism, and there is weak role of the media in the propagating the purpose of tourism and promoting tourism in Syria.